Analisis pengaruh industri pariwisata terhadap PDRB Jawa Tengah era pandemi covid-19 - Andriyani, Nur; Salam, Annisa Nur (Nur Science Institute, 2022)
This study aims to analyze the influence of the tourism industry on PDRB in 35 districts/cities of Central Java during the 2020–2021 COVID-19 pandemic era. Secondary data is obtained from the Central Statistics Agency (BPS). The independent variables used are the number of tourist attractions, the number of domestic tourists, the number of foreign tourists, the number of restaurants, and the number of hotels and other accommodations. The dependent variable is the regional income of the tourism sector. The research method used is panel data regression with a fixed-effect model. The study results partially show that the variable number of tourist attractions and the number of hotels and other accommodations positively and significantly affect GRDP. The variable number of restaurants and the number of foreign tourists negatively and significantly affect GRDP. At the same time, domestic tourists have no significant effect on GRDP. Simultaneously, the variables of the number of tourist attractions, the number of domestic tourists, the number of foreign tourists, the number of restaurants, and the number of hotels and other accommodations affect the GRDP. Strenuous efforts are needed for the tourism industry to restore tourism performance to be more optimal in contributing to the economy.